Analisis Kesiapan EMKM dalam Penerapan Akuntansi Berdasarkan SAK EMKM: Studi Kasus EMKM Djati Laundry - Haryanti, Novia Putri; Astriani, Devi; Puspitasari, Meliana (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Readiness is the state of someone who is ready to apply SAK EMKM in his business and seen from the perspective of conditions, desires, and knowledge about SAK EMKM. This study intends to understand the level of readiness of EMKM Djati Laundry in the application of accounting based on SAK EMKM with service business fields located in East Telukjambe District. This study collected primary and secondary data through in-depth interviews, observations and documentation on EMKM Djati Laundry in East Telukjambe District that meets the requirements as micro, small and medium enterprises. Using qualitative descriptive methodology combined with Miles and Huberman's interactive analysis methods. According to the research findings, Djati Laundry's financial statements are not ready to implement SAK EMKM. This is due to their ignorance of SAK EMKM's knowledge, their financial records still use the cash basis method, due to their lack of experience in preparing financial statements in accordance with financial accounting standards, and the absence of staff members dedicated to doing bookkeeping.